2020
DOI: 10.15585/mmwr.mm6940e3
|View full text |Cite
|
Sign up to set email alerts
|

Trends in COVID-19 Incidence After Implementation of Mitigation Measures — Arizona, January 22–August 7, 2020

Abstract: On October 6, 2020, this report was posted as an MMWR Early Release on the MMWR website (https://www.cdc.gov/mmwr). Mitigating the spread of SARS-CoV-2, the virus that causes coronavirus disease 2019 (COVID-19), requires individual, community, and state public health actions to prevent person-to-person transmission. Community mitigation measures can help slow the spread of COVID-19; these measures include wearing masks, social distancing, reducing the number and size of large gatherings, pausing operation of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 4 publications
5
68
0
Order By: Relevance
“…The findings in this report are consistent with declines in COVID-19 cases observed in 15 states and the District of Columbia, which mandated masks, compared with states that did not have mask mandates ( 7 ). Mask requirements were also implemented as part of a multicomponent approach in Arizona, where COVID-19 incidence stabilized and then decreased after implementation of a combination of voluntary and enforceable community-level mitigation strategies, including mask requirements, limitations on public events, enhanced sanitation practices, and closures of certain services and businesses ( 8 ). The combining of community-level mitigation strategies including physical distancing and enhanced hygiene practices, in addition to consistent and correct use of masks, is a CDC-recommended approach.…”
Section: Discussionmentioning
confidence: 99%
“…The findings in this report are consistent with declines in COVID-19 cases observed in 15 states and the District of Columbia, which mandated masks, compared with states that did not have mask mandates ( 7 ). Mask requirements were also implemented as part of a multicomponent approach in Arizona, where COVID-19 incidence stabilized and then decreased after implementation of a combination of voluntary and enforceable community-level mitigation strategies, including mask requirements, limitations on public events, enhanced sanitation practices, and closures of certain services and businesses ( 8 ). The combining of community-level mitigation strategies including physical distancing and enhanced hygiene practices, in addition to consistent and correct use of masks, is a CDC-recommended approach.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they did not adjust for epidemics beginning at different time points in different locations or socio-demographic variables ( 14 ). The studies by Kaufman et al, Chernozhukov et al and Gallaway et al all suggest wearing masks in public locations is beneficial ( 20 , 21 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypothetical mask models support these results and one such study suggested that even weak (ineffective) masks could be useful in curbing disease transmission ( 22 ). It has also been noted that widespread implementation and enforcement of sustained community mitigation measures helped with mitigation of COVID-19, noting a decline in rates once measures were implemented ( 23 ). Similarly, a study looking at daily county-level COVID-19 growth rates in 15 states and Washington, D.C., estimated that more than 200,000 COVID-19 cases could have been averted by May 22, 2020 if utilizing masks in public had been mandatory in all locations ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…31 32 Our observed geographic disparities in COVID-19 preventive behaviours may also be a reflection of variability in state or local policies regarding COVID-19 preventive behaviours across the individuals residing in US states and counties that have implemented mandatory COVID-19 preventive behaviours, including stay-at-home orders, social distancing and mandatory mask use in public, are more likely to exhibit positive individual-level COVID-19 preventive behaviours. [33][34][35] Inequities in ability or willingness to practice COVID-19 preventive behaviours may lead to inequitable risk and morbidity of COVID-19 among these at-risk groups. Future research should focus on the impact of state-level COVID-19 prevention policies to evaluate area-level differences in individual preventive behaviours and to disentangle whether certain demographics of US adults are either unwilling or unable to adhere to recommended guidelines.…”
Section: Discussionmentioning
confidence: 99%